2016
DOI: 10.1589/jpts.28.2430
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic analysis of tandem gait on a sine wave walkway

Abstract: [Purpose] The purpose of this study was to ascertain the kinematic characteristics on a horizontal plane, including knee joint rotation, when walking with a tandem gait on a sine wave walkway. [Subjects and Methods] Eighteen healthy adults were enrolled as subjects in this study. They walked with a tandem gait on a sine wave walkway. A three-dimensional motion analysis system was used to record data and calculate the trunk, hip joint, and knee joint rotation angles. [Results] The rotation angle ranges for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Additionally, it has been suggested that, for tandem gait on the sine-wave-shaped walking path, the knee joint rotational angle8 ) and muscular activity of rotator muscle group are important. In other words, for change of direction, the muscular tension of the agonist muscle and the antagonist muscle are important, as is the inertial force.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has been suggested that, for tandem gait on the sine-wave-shaped walking path, the knee joint rotational angle8 ) and muscular activity of rotator muscle group are important. In other words, for change of direction, the muscular tension of the agonist muscle and the antagonist muscle are important, as is the inertial force.…”
Section: Discussionmentioning
confidence: 99%
“…1. Tandem gait on a sine wave walkway.). We conducted motion dynamic analysis of each body segment, particularly knee joint rotational movement, at a change of direction for tandem gait on a sine-wave-shaped walking path8 ) . In the experiment, the body trunk rotation angle was 23.3°, the hip joint rotation angle was 53.3°, and the knee joint rotation angle was 47.3°, whereas the knee joint rotation angle is similar to the value used in earlier studies9,10,11 ) .…”
Section: Introductionmentioning
confidence: 99%